The four pathways of assertiveness: a multidimensional framework for enhancing individual well-being - Naoki Yoshinaga; Scott Cooper (Frontiers in Psychology)
This paper introduces a broader theoretical framework for assertiveness that integrates traditional social assertiveness with three additional dimensions: behavioral, emotional, and mental assertiveness. We delineate four distinct yet interrelated pathways of assertiveness, applying common, non-technical terminology: “speaking up” (social), “jumping in” (behavioral), “embracing compassion” (emotional), and “accepting life” (mental). These dimensions are situated within an integrative framework aimed at enhancing individual well-being through intentional and context-sensitive agency. Drawing from existing psychological theories (e.g., grit, self-regulation, empathy), we clarify how each facet is differentiated from related constructs or theories. Furthermore, we outline practical directions for empirical testing, including candidate self-report measures, behavioral tasks, and qualitative assessments. The proposed model offers a multidimensional basis for future research and intervention development.